1987
DOI: 10.1017/s0317167100026627
|View full text |Cite
|
Sign up to set email alerts
|

CT Findings in Late-Onset Epilepsy

Abstract: We reviewed the CT findings of 387 patients with new-onset seizures after the age of 50. Seizures were generalized in 212 patients, focal in 160, and indeterminant in 15. CT scanning revealed cerebral atrophy in 113 cases, ischemic lesions in 75, cerebral neoplasms in 20, and no abnormality in 177 cases. Tumours were found in only three patients with generalized seizures, and all three had focal neurological deficits at the time of CT diagnosis, while 17 neoplasms were discovered in patients with a focal seizu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
3
1
0
1
Order By: Relevance
“…4 de la Sayette et al, in a study on 387 patients over 50 years of age with late-onset epilepsy, reported that most patients for whom CT scan was performed had either normal results or evidence of cerebral atrophy. 9 In another study on children hospitalized due to afebrile seizure in Tehran, Iran, 90% of the CT scans were reported as normal, which is in accordance with our study. 10 On the other hand, Smith et al in 2013 studied 309 patients with their first-onset seizure in South Africa.…”
Section: Discussionsupporting
confidence: 91%
“…4 de la Sayette et al, in a study on 387 patients over 50 years of age with late-onset epilepsy, reported that most patients for whom CT scan was performed had either normal results or evidence of cerebral atrophy. 9 In another study on children hospitalized due to afebrile seizure in Tehran, Iran, 90% of the CT scans were reported as normal, which is in accordance with our study. 10 On the other hand, Smith et al in 2013 studied 309 patients with their first-onset seizure in South Africa.…”
Section: Discussionsupporting
confidence: 91%
“…The direct admission of head injury cases to the neurosurgical department could be the reason behind this phenomenon, as it would make it difficult for us to observe posttraumatic immediate/early onset of epilepsy. Nonetheless, it is comparable to 4.10% cases in the Rochester, Minnesota study 8 In the present study, 28% cases were of idiopathic epilepsy, which is somewhat comparable to 35% in the study done by Rigatti M et al 6 and 44% in the study done by Pradeep P. V. et al 5 In the present study, generalized seizure was the most common seizure type with 58.67% cases while partial seizure was observed in 41.33% cases; which is comparable to 58.4% and 41.6% respectively in the study conducted by Lopez et al 11 In the present study, abnormal CT scan of brain was seen in 65.33% cases, which is comparable to 62% in the study done by De La Sayette V et al 12 and 72% in the study done by Medina et al 13…”
Section: Discussionsupporting
confidence: 82%
“…Cerebral vascular disease appears to be the most frequently identified cause of late-onset epilepsy, while cerebral neoplasms are uncommon. [9] In the present study, Tuberculoma was found to be present among in 18 patients with partial seizures. Cerebral infarct was found to be present in 10 patients with partial seizures and among 15 patients with generalized seizures.…”
Section: Original Articlesupporting
confidence: 50%